Online submission, feedback and grading of assessment: what do academic staff really think? - Emma Mayhew; Vicki Holmes; Madeleine Davies; Yota Dimitriadi (Association for Learning Technology, 2022)
The move to institution-wide adoption of online submission, feedback and grading is increasing significantly within the Higher Education sector. This transition is predominantly driven by the need to improve the student assessment experience, but some institutions now also cite the need to improve the staff assessment experience. Existing studies, however, provide seemingly contradictory evidence surrounding this online marking experience. This article adopts a mixed methods approach to explore academic staff preferences of the assessment experience within a UK-based institution following adoption of online submission, feedback and grading during 2017-2018. It finds that although the majority of colleagues prefer to mark and provide feedback online, the process of marking electronically is highly individual. Online marking is not just a single practice but a set of varied, rich approaches, influenced by individual marker perceptions, preferences and previous experiences, and is often highly emotive. Changes to existing marking practices are seen simultaneously as both challenging and liberating by cohorts of markers. Drawing on the results of a detailed staff survey, this article identifies seven themes that are influential to that experience. These findings have significant implications for how institutions manage change to large-scale adoption of online marking.